Surgical Repair of Atrial Septal Defect with Severe Pulmonary Hypertension: A Case Report: ASD with severe pulmonary hypertension (Cardiovascular Journal, 2024)
This case report details the successful surgical repair of an atrial septal defect (ASD) in a 28-year-old female with severe pulmonary arterial hypertension (PAH), who presented with  dyspnea, fatigue, and palpitations. The patient had a large secundum ASD (26 mm size) with bi-directional shunt and severe PAH, with a Pulmonary Arterial Systolic Pressure (PASP) of 107 mmHg and Mean Pulmonary Arterial Pressure (mPAP) of 57 mmHg, as revealed by echocardiography. The patient was optimized medically with diuretics, oxygen, and pulmonary vasodilators (Sildenafil & Ambrisentan), and was deemed eligible for surgical closure of the ASD. A pericardial patch was used to close the defect, and the patient's postoperative recovery was uneventful. Follow-up echocardiography showed a significant reduction in mPAP and right ventricular size. Although surgical closure of an ASD with severe PAH is a high-risk procedure, it can be safely performed in carefully selected patients with appropriate preoperative evaluation, medical optimization, and careful surgical technique. Timely closure of the defect can result in a considerable improvement in the patient's hemodynamic status and quality of life.Cardiovasc j 2024; 16(2): 110-113